Reducing intestinal digestion and absorption of fat using a nature-derived biopolymer : interference of triglyceride hydrolysis by nanocellulose - DeLoid, Glen M. (2019)
Engineered nanomaterials are increasingly added to foods to improve quality, safety, or nutrition. Here we report the ability of ingested nanocellulose (NC) materials to reduce digestion and absorption of ingested fat. In the small intestinal phase of an acellular simulated gastrointestinal tract, the hydrolysis of free fatty acids (FFA) from triglycerides (TG) in a high-fat food model was reduced by 48.4% when NC was added at 0.75% w/w to the food, as quantified by pH stat titration, and by 40.1% as assessed by fluorometric FFA assay. Furthermore, translocation of TG and FFA across an in vitro cellular model of the intestinal epithelium was significantly reduced by the presence of 0.75% w/w NC in the food (TG by 52%, and FFA by 32%). Finally, in in vivo experiments, the postprandial rise in serum TG one hour after gavage with the high fat food model was reduced by 36% when 1.0% w/w NC was administered with the food. As revealed by scanning electron microscopy and molecular dynamics studies, the primary mechanisms for this effect appear to include coalescence of fat droplets on fibrillar NC (CNF) fibers, resulting in a reduction of available surface area for lipase binding, and sequestration of bile salts, causing impaired interfacial displacement of proteins at the lipid droplet surface, and impaired solubilization of lipid digestion products. Together these findings suggest a potential use for NC, as a food additive or supplement, to reduce absorption of ingested fat and thereby assist in weight loss and the management of obesity.